2013
DOI: 10.1083/jcb.201303035
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic NMDA receptor stimulation activates PP1 by inhibiting its phosphorylation by Cdk5

Abstract: Synaptic stimulation promotes proteasome-dependent degradation of p35, inactivation of Cdk5, and decreased phosphorylation of PP1, allowing PP1 to act in the induction of long-term depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 61 publications
4
30
0
Order By: Relevance
“…These results agree with previous studies demonstrating that tPA has a homeostatic effect in the synapse under physiological and pathological conditions (Wu et al, 2012, 2013b; Yepes, 2015). Importantly, our data indicate that as shown by others (Hou et al, 2013) the baseline levels of PP1 phosphorylated at T35 are almost undetectable, and that tPA does not have an effect on I-1 phosphorylation at T35. Instead, our results indicate that tPA has a direct effect on PP1 phosphorylation at T320.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…These results agree with previous studies demonstrating that tPA has a homeostatic effect in the synapse under physiological and pathological conditions (Wu et al, 2012, 2013b; Yepes, 2015). Importantly, our data indicate that as shown by others (Hou et al, 2013) the baseline levels of PP1 phosphorylated at T35 are almost undetectable, and that tPA does not have an effect on I-1 phosphorylation at T35. Instead, our results indicate that tPA has a direct effect on PP1 phosphorylation at T320.…”
Section: Discussionsupporting
confidence: 81%
“…Recent studies have found that Cdk-5-induced phosphorylation of PP1 at T320 (pPP1) is a calcineurin-independent mechanism for PP1 inactivation that plays a central role in the development of synaptic plasticity (Hou et al, 2013). Thus, to investigate whether PP1 inactivation by its phosphorylation at T320 mediates tPA-induced CaMKIIα phosphorylation and recruitment to the PSD in neurons with low baseline levels of pCaMKIIα, we studied the expression of pPP1 (T320) in PSD extracts prepared from Wt cerebral cortical neurons treated with 5 nM of tPA or vehicle (control) in the presence or absence of the Cdk5 inhibitor Rosc.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further confirm these results, we used an alternative method of stimulation. It is known that synaptic NMDA receptors can be activated by treating neurons with a combination of a potassium channel antagonist and a GABA A receptor antagonist [ 27 , 28 , 29 ]. Thus, we stimulated hippocampal neurons with PTX and 4-aminopyridine (4-AP), a potassium channel antagonist.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that stimulation of synaptic NMdARs leads to a decrease in Cdk5 activity. 35 NO production, and in turn, Cdk5 SNO activate Cdk5. MK-801 blocks both synaptic NMdARs and NMdAR-PSd-95-nNOS-NO pathway.…”
Section: Discussionmentioning
confidence: 99%